DEVELOPMENT OF PHYSICS MAGAZINE LEARNING MEDIA BASED ON ETHNOSCIENCE TO IMPROVE SCIENCE LITERACY IN JUNIOR HIGH SCHOOL STUDENTS - najila; Alfarizi, Zakaria; Prasetyo, Erwin (JURNAL PEMBELAJARAN FISIKA, 2025)
The low scientific literacy of junior high school students is caused by the lack of interesting and contextual learning media. This study aims to develop an ethnoscience-based physics magazine as a learning media integrated with local culture. The method used is Research and Development (R&D) with the ADDIE model. Validation was carried out by media and material experts with very good and good results. The magazine was implemented in class VIII MTs At-Taqwa Beru. The results of the pretest and posttest showed a significant increase, from an average of 43.25 to 70, with a significance value of 0.000 and an effect size of 1.68. As many as 75% of students achieved the KKM. The output of this study is an ethnoscience-based physics magazine product that effectively improves students' scientific literacy through a local cultural approach.